Ebola Interventions : Listen to Communities - Kutalek, Ruth; Wang, Shiyong; Fallah, Mosoka; Sanford Wesseh, Chea; Gilbert, Jeffrey (Elsevier, 2015)
Active case finding (which includes contact tracing) ensures early identification and prompt isolation of potential cases of Ebola virus disease (EVD), leading to successful interruption of transmission in a community. Failure to identify and follow up all contacts could be enough to keep the outbreak going. In late November, 2014, Liberia's Ministry of Health and WHO Liberia did a rapid qualitative assessment (supported by the World Bank) of the perceptions of selected communities in Monrovia on an incentive scheme that intends to increase the reporting of EVD cases.